Analysis of combined heat and mass transfer of water-vapor in a cylinderical zeolite adsorber
Jn this paper, the combined heat and mass transfer of water-vapor into a cylindrical zeolite adsorber has been numerically simulated The twodimensional heat and mass transfer equations are numerically solved using gPROMS program - a general Process Modeling System [J] program, inserting the proper initial and boundary conditions to the model. The centered finitedifference method (CFDM) approximation is employed in solving the two-dimensional partial differential equations. The validity of the developed model has been checked against an experimental study [2